All-solid-state battery, method for manufacturing same, and vehicle
By using a porous network formed by entangled fibrous carbon and coating of inorganic electrolytes in an all-solid state battery, the problem of insufficient energy density and output performance of the all-solid state battery is solved, and the charging/discharging efficiency and life characteristics of the battery are improved.
Patent Information
- Application Number
- CN202410368710.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-12
- Filing Date
- 2024-03-28
- Publication Date
- 2025-04-15
AI Technical Summary
The existing all-solid state batteries cannot reach the level of traditional liquid electrolyte lithium-ion batteries in terms of energy density and output performance, and the anode-free all-solid state batteries have the risk of performance deterioration in terms of uneven lithium precipitation and irreversible reactions.
The surface of the coating is suitably coated with the inorganic electrolyte surface by inserting a coating with excellent ionic conductivity and electrical conductivity between the anode current collector and the solid electrolyte layer, which consists of a porous network formed by interlaced fibrous carbon and an inorganic electrolyte surface.
The charging/discharge efficiency and life characteristics of all solid-state batteries are improved, and the growth of lithium dendritics is inhibited by uniform precipitation of lithium ions, thereby improving the energy density and output performance of the battery.
Smart Images

Figure CN119833766A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an all-solid-state battery and a method for manufacturing the same, wherein the all-solid-state battery includes a coating configured such that a surface of a porous network formed by entangled fibrous carbon is coated with an inorganic electrolyte, thereby improving its charge / discharge efficiency and life characteristics. Background Art
[0002] Secondary batteries capable of charge and discharge are used not only for small electronic devices such as mobile phones, laptops, etc., but also for large transportation vehicles such as hybrid vehicles, electric vehicles, etc. Therefore, development of secondary batteries having higher stability and energy density is required.
[0003] Most existing secondary batteries have organic solvent (organic liquid electrolyte)-based cells, showing limitations in improving stability and energy density.
[0004] Meanwhile, all-solid-state batteries using inorganic solid electrolytes have recently attracted attention because the batteries can be manufactured in a safer and simpler form based on a technology that excludes organic solvents.
[0005] However, all-solid-state batteries have limitations because their energy density and output performance cannot reach those of lithium-ion batteries using conventional liquid electrolytes. With the goal of solving these problems, improvements in electrodes for all-solid-state batteries are being intensively studied.
[0006] In particular, graphite is mainly used as the anode of all-solid-state batteries. Therefore, a solid electrolyte with a high specific gravity must be added in excess with graphite to obtain ionic conductivity, which results in a very low energy density per unit weight compared to lithium-ion batteries. Moreover, when lithium metal is used as the anode, there are technical limitations in terms of price competitiveness and large-area formation.
[0007] Currently, a lot of research has been conducted on high energy density all-solid-state batteries, and in particular, anode-free all-solid-state batteries have attracted attention. Anode-free all-solid-state batteries are batteries that deposit lithium on an anode current collector instead of using an anode active material such as graphite or lithium metal.
[0008] Anode-free all-solid-state batteries can theoretically achieve high energy density, but some problems may arise, such as the possibility of short circuits due to uneven precipitation of lithium and battery performance degradation due to increased irreversible reactions. Summary of the invention
[0009] In one aspect, an all-solid-state battery is provided in which a coating having excellent ionic conductivity and electrical conductivity is inserted between an anode current collector and a solid electrolyte layer in a balanced manner, and a method for manufacturing the all-solid-state battery is provided.
[0010] The purpose of the present disclosure is not limited to the foregoing content. Through the following description, the purpose of the present disclosure will be clearly understood and achieved by the devices described in the claims and their combinations.
[0011] On the one hand, an all-solid-state battery is provided, comprising: a) an anode current collector; b) a coating disposed on the anode current collector; c) a solid electrolyte layer disposed on the coating; d) a cathode active material layer disposed on the solid electrolyte layer; and e) a cathode current collector disposed on the cathode active material layer, wherein the coating comprises a porous network comprising fibrous carbon.
[0012] In some aspects, the porous network can be formed by or can be obtained by intertwining fibrous carbon and an inorganic electrolyte. In various aspects, the inorganic electrolyte can suitably coat at least a portion of the surface of the network. One aspect of the present disclosure provides an all-solid-state battery, comprising an anode current collector, a coating disposed on the anode current collector, a solid electrolyte layer disposed on the coating, a cathode active material layer disposed on the solid electrolyte layer, and a cathode current collector disposed on the cathode active material layer, wherein the coating comprises a porous network formed by intertwining fibrous carbon and an inorganic electrolyte coating at least a portion of the surface of the network.
[0013] In an exemplary embodiment, the coating layer may have a thickness of 5 μm to 30 μm.
[0014] Preferably, the thickness of the coating may be greater than 5 μm and less than 20 μm.
[0015] In exemplary embodiments, the fibrous carbon may include at least one selected from the group consisting of carbon nanofibers, carbon nanotubes, vapor-grown carbon fibers, and combinations thereof.
[0016] In an exemplary embodiment, the coating may not include a conductive material or an adhesive.
[0017] In exemplary embodiments, the inorganic electrolyte may be sulfur-based.
[0018] In exemplary embodiments, the sulfur-based inorganic electrolyte may be lithium phosphorus sulfur chloride (LPSCl).
[0019] Another aspect of the present disclosure provides a method for manufacturing an all-solid-state battery, comprising: preparing a porous network formed by intertwining fibrous carbon; obtaining an intermediate by immersing the porous network in a solution containing an inorganic electrolyte; obtaining a coating by heat treating the intermediate, and obtaining an all-solid-state battery by stacking an anode current collector, a coating, a solid electrolyte layer, a cathode active material layer, and a cathode current collector, wherein the coating comprises a porous network and an inorganic electrolyte coating at least a portion of a surface of the porous network.
[0020] In an exemplary embodiment, the porous network can be prepared by direct spinning.
[0021] In exemplary embodiments, the fibrous carbon may include at least one selected from the group consisting of carbon nanofibers, carbon nanotubes, vapor-grown carbon fibers, and combinations thereof.
[0022] In exemplary embodiments, the solution may not include a binder or a conductive material.
[0023] In exemplary embodiments, the solution may include about 0.3 wt % to about 5 wt % of the inorganic electrolyte.
[0024] In exemplary embodiments, the solution may be obtained by dissolving an inorganic electrolyte in a solvent, and the solvent may include at least one selected from the group consisting of an alcohol solvent, an organic solvent, a reaction solvent, and a combination thereof.
[0025] In an exemplary embodiment, the inorganic electrolyte may include a sulfur-based inorganic electrolyte. The sulfur-based inorganic electrolyte may be lithium phosphorus sulfur chloride (LPSCl).
[0026] Alcohol solvents may include ethanol, or other alkyl alcohols such as propanol, or other polar solvents.
[0027] The organic solvent may include one selected from the group consisting of acetonitrile, xylene, and combinations thereof, or other suitable solvents such as toluene, dichloromethane, and the like.
[0028] The reaction solvent may include tetrahydrofuran or other suitable organic solvents.
[0029] In an exemplary embodiment, the porous network may be immersed in the solution for about 5 to about 30 minutes.
[0030] In exemplary embodiments, the method may further include drying the intermediate at room temperature after obtaining the intermediate.
[0031] In exemplary embodiments, the heat treatment of the intermediate may be performed at about 50° C. to about 450° C. In addition, the heat treatment of the intermediate may be performed for about 6 to about 24 hours.
[0032] As discussed, in various aspects, the present methods and systems suitably include the use of a controller or processor.
[0033] As used herein, the term "all-solid-state battery" includes or refers to a rechargeable battery (including a secondary battery) that includes a solid electrolyte, such as a gel or polymer (cured), which may include an ionomer and other electrolytic components for transferring ions between the electrodes of the battery. In one aspect, an "all-solid-state battery" may include a secondary battery, including a secondary battery used with a vehicle.
[0034] In another aspect, there is provided a vehicle comprising a battery as disclosed herein.
[0035] Other aspects of the invention are disclosed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The above-mentioned and other features of the present disclosure will now be described in detail with reference to certain exemplary embodiments of the present disclosure illustrated in the accompanying drawings, which are given hereinafter by way of illustration only and thus do not limit the present disclosure, and in which:
[0037] Figure 1 schematically illustrates an all-solid-state battery according to the present disclosure;
[0038] Figure 2 shows a scanning electron microscope (SEM) image of the coating according to Preparation Example 1;
[0039] Figure 3 shows a SEM image of a porous network according to Comparative Preparation Example 1;
[0040] Figure 4 and Figure 5 The BET specific surface area analysis results of the coating according to Preparation Example 1 are shown respectively;
[0041] Figure 6 and Figure 7 The BET specific surface area analysis results of the porous network according to Comparative Preparation Example 1 are shown respectively;
[0042] Figure 8 and Fig. 9 Analytical results of the coating according to Preparation Example 1 using mercury porosimetry are shown respectively;
[0043] Fig.10 and Fig.11 The analysis results of the porous network according to Comparative Preparation Example 1 using mercury porosimetry are shown respectively;
[0044] Fig.12 The analysis results of the cycle characteristics of the all-solid-state batteries according to Comparative Examples 1 to 3 are shown;
[0045] Fig.13 The analysis results of the cycle characteristics of the all-solid-state battery according to Comparative Example 4 are shown;
[0046] Fig.14 The analysis results of the cycle characteristics of the all-solid-state batteries according to Examples 1 to 3 are shown;
[0047] Fig.15 The analysis results of the cycle characteristics of the all-solid-state batteries according to Example 1 and Comparative Example 1 are shown;
[0048] Fig.16 shows the evaluation results of the room temperature operation characteristics of the all-solid-state battery according to Comparative Example 1; and
[0049] Fig.17 The results of evaluating the room temperature operation characteristics of an all-solid-state battery using a carbon nanotube sheet as an anode current collector are shown. DETAILED DESCRIPTION
[0050] From the following preferred embodiments in conjunction with the accompanying drawings, the above and other purposes, features and advantages of the present disclosure will be more clearly understood. However, the present disclosure is not limited to the embodiments disclosed herein and can be modified into different forms. These embodiments are provided to thoroughly explain the present disclosure and fully convey the spirit of the present disclosure to those skilled in the art.
[0051] It should be understood that the term "vehicle" or "vehicle-based" or other similar terms as used herein include a broad range of motor vehicles, such as passenger cars including sport utility vehicles (SUVs), buses, trucks, various commercial vehicles, water vehicles (including various boats and ships), aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid electric vehicles, hydrogen-powered vehicles, and other alternative fuel vehicles (e.g., fuels derived from resources other than petroleum). As mentioned herein, a hybrid vehicle is a vehicle having two or more power sources, for example, gasoline-powered and electric-powered vehicles.
[0052] The terms used herein are only used for the purpose of describing specific embodiments, and are not intended to limit the present disclosure. As used herein, unless the context clearly indicates otherwise, the singular forms "one", "an" and "the" are intended to also include plural forms. These terms are only intended to distinguish one component from another component, and these terms do not limit the nature, order or sequence of the constituent components. It should also be understood that the terms "comprises" and / or "comprising" when used in this specification specify the presence of the features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or their combinations. As used in this article, the term "and / or" includes any and all combinations of one or more related listed items. Throughout the specification, unless explicitly described to the contrary, the word "comprise" and variants such as "comprises" or "comprising" will be understood to imply the inclusion of the elements, but do not exclude any other elements. In addition, the terms “unit”, “device”, “instrument”, and “module” described in the specification mean a unit for processing at least one function and operation, and may be implemented by hardware components or software components and a combination thereof.
[0053] Unless otherwise specified or apparent from the context, as used herein, the term "about" should be understood to be within the normal tolerance range in the art, such as within 2 standard deviations of the mean. "About" can be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the value. Unless the context clearly indicates otherwise, all numerical values provided herein are modified by the term "about".
[0054] Moreover, it will be understood that when an element such as a layer, film, region, or sheet is referred to as being "on" another element, it can be directly on the other element or intervening elements may be present therebetween. Similarly, when an element such as a layer, film, region, or sheet is referred to as being "under" another element, it can be directly under the other element or intervening elements may be present therebetween.
[0055] Unless otherwise specified, all numerals, values, and / or representations used herein to represent components, reaction conditions, polymer compositions, and the amount of mixtures should be considered approximate values, including various uncertainties that affect measurement that occur inherently when obtaining these values, and therefore should be understood in all cases as being modified by the term "about". In addition, when a numerical range is disclosed in this specification, unless otherwise indicated, the range is continuous and includes all values from the minimum value of the range to its maximum value. In addition, when such a range involves integer values, unless otherwise indicated, the range includes all integers from the minimum value to the maximum value.
[0056] In this specification, when a range is described for a variable, it will be understood that the variable includes all values described in the range, including the endpoints. For example, a range of "5 to 10" should be understood to include any sub-ranges, such as 6 to 10, 7 to 10, 6 to 9, 7 to 9, etc., as well as individual values of 5, 6, 7, 8, 9 and 10, and should also be understood to include any values between valid integers in the range, such as 5.5, 6.5, 7.5, 5.5 to 8.5, 6.5 to 9, etc. In addition, for example, a range of "10% to 30%" will be understood to include sub-ranges, such as 10% to 15%, 12% to 18%, 20% to 30%, etc., and all integers, including values 10%, 11%, 12%, 13%, etc. up to 30%, and will also be understood to include any values between valid integers in the range, such as 10.5%, 15.5%, 25.5%, etc.
[0057] All-solid-state battery
[0058] Figure 1 The all-solid-state battery according to the present disclosure is schematically shown. Figure 1 According to one aspect of the present disclosure, an all-solid-state battery may include: an anode current collector 10, a coating 20 disposed on the anode current collector 10, a solid electrolyte layer 30 disposed on the coating 20, a cathode active material layer 40 disposed on the solid electrolyte layer 30, and a cathode current collector 50 disposed on the cathode active material layer 40, wherein the coating 20 may include a porous network formed by intertwining fibrous carbon and an inorganic electrolyte coating at least a portion of a surface of the network.
[0059] The anode current collector 10 may be a plate-type substrate having electrical conductivity. Specifically, the anode current collector 10 may be in the form of a sheet, a film, or a foil.
[0060] The anode current collector 10 may include a material that does not react with lithium. Specifically, the anode current collector 10 may include at least one selected from the group consisting of nickel (Ni), copper (Cu), stainless steel, and a combination thereof.
[0061] The thickness of the anode current collector 10 is not particularly limited, and may be, for example, 1 μm to 500 μm.
[0062] During charging of the all-solid-state battery, lithium ions released from the cathode active material layer 40 may move toward the coating layer 20 through the solid electrolyte layer 30. The lithium ions reaching the coating layer 20 may be stored in the form of metal at the interface between the coating layer 20 and the solid electrolyte layer 30 or inside the coating layer 20 by a reduction reaction with electrons emitted from the anode current collector 10.
[0063] Thus, since the coating layer 20 includes both an inorganic electrolyte having high ionic conductivity and fibrous carbon having high electrical conductivity, lithium can be uniformly precipitated on the coating layer 20. Therefore, the growth of lithium dendrites due to repeated charging and discharging of the all-solid-state battery can be suppressed and its life characteristics can be improved.
[0064] In addition, according to the present disclosure, since an anode active material capable of alloying with lithium is not included, the charging and discharging of the all-solid-state battery can occur through oxidation / reduction reactions of lithium ions rather than alloying reactions of lithium, enabling it to operate at relatively low temperatures. The all-solid-state battery according to the present disclosure may be an anode-free battery that does not include an anode active material.
[0065] In addition, the coating 20 may include a network formed by intertwining fibrous carbon. The network may be porous due to voids or pores, which are spaces in the fibrous carbon. When the all-solid-state battery is charged, the network may provide space for storing lithium precipitated in the form of metal by reducing lithium ions.
[0066] In exemplary embodiments, the fibrous carbon may include at least one selected from the group consisting of carbon nanofibers, carbon nanotubes, vapor-grown carbon fibers, and combinations thereof.
[0067] In an exemplary embodiment, the thickness of the coating 20 may be 5 μm to 30 μm. Preferably, the thickness of the coating 20 may be greater than 5 μm and less than 20 μm. If the thickness of the coating 20 is 5 μm or less, when the all-solid-state battery is charged, the capacity of the battery may decrease due to insufficient space for lithium ions to be reduced in metal form. On the other hand, if the thickness of the coating 20 is 20 μm or more, the energy density may decrease, and some lithium precipitated in the coating 20 during charging may be irreversibly stored, thereby deteriorating the cycle characteristics.
[0068] Meanwhile, the average diameter D of the fibrous carbon not coated with the inorganic electrolyte is 50It may be 20 nm or more, for example, 20 nm to 30 nm. In an exemplary embodiment, the average diameter D of the fibrous carbon coated with the inorganic electrolyte according to the present disclosure is 50 It may be 25 nm or more. Here, the average diameter of the fibrous carbon may mean the average diameter of a bundle in which a plurality of fibers are gathered. If the average diameter of the fibrous carbon is less than 25 nm, this may mean that the surface of the porous network formed by entanglement of the fibrous carbon is not properly coated with the inorganic electrolyte.
[0069] The upper limit of the average diameter of the fibrous carbon is not particularly limited, and may be, for example, 25 nm to 1000 nm, or 35 nm to 100 nm. The average diameter of the fibrous carbon coated with the inorganic electrolyte may be calculated based on the average diameter D of the fibrous carbon not coated with the inorganic electrolyte. 50 and the coating thickness of the inorganic electrolyte.
[0070] In an exemplary embodiment, the coating 20 may not include a conductive material or a binder. The coating 20 according to the present disclosure includes a porous network formed by entanglement of fibrous carbon having high electrical conductivity, and thus may not include an additional conductive material to increase electrical conductivity. Moreover, the coating 20 includes an inorganic electrolyte coating at least a portion of the surface of the network, thereby increasing the roughness of the surface of the network, and thus may not include an additional binder.
[0071] Meanwhile, the inorganic electrolyte may be a solid electrolyte having lithium ion conductivity. The inorganic electrolyte may include an oxide-based inorganic electrolyte, a sulfide-based inorganic electrolyte, and the like. Preferably, a sulfide-based inorganic electrolyte having high lithium ion conductivity may be used. The sulfide-based inorganic electrolyte is not particularly limited, but embodiments thereof may include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B2S3-LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one selected from Ge, Zn, and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and M is any one selected from P, Si, Ge, B, Al, Ga, and In), Li 10 G 2 S 12 wait.
[0072] Examples of oxide-based inorganic electrolytes may include perovskite-type LLTO (Li 3x La 2 / 3-x TiO 3 ), phosphate-based NASICON-type LATP (Li 1+x Al x Ti 2-x (PO 4 ) 3 )wait.
[0073] The solid electrolyte layer 30 may be disposed between the cathode active material layer 40 and the coating layer 20 , and may include a solid electrolyte having lithium ion conductivity.
[0074] The solid electrolyte may include at least one selected from the group consisting of an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer electrolyte, and a combination thereof. Preferably, a sulfide-based solid electrolyte having high lithium ion conductivity may be used.
[0075] The sulfide-based solid electrolyte is not particularly limited, but embodiments thereof may include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B2S3-LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one selected from Ge, Zn, and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS2 -Li x MO y (wherein x and y are positive numbers, and M is any one selected from P, Si, Ge, B, Al, Ga, and In), Li 10 G 2 S 12 wait.
[0076] Examples of oxide-based solid electrolytes may include perovskite-type LLTO (Li 3x La 2 / 3-x TiO 3 ), phosphate-based NASICON-type LATP (Li 1+x Al x Ti 2-x (PO 4 ) 3 )wait.
[0077] Examples of the polymer electrolyte may include a gel polymer electrolyte, a solid polymer electrolyte, and the like.
[0078] The solid electrolyte layer 30 may further include a binder. Examples of the binder may include butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), and the like.
[0079] Here, the solid electrolyte included in the solid electrolyte layer 30 and the inorganic electrolyte included in the coating layer 20 may be the same or identical to each other.
[0080] The cathode active material layer 40 can reversibly intercalate and deintercalate lithium ions, and may include a cathode active material, a conductive material, a binder, etc. Also, some solid electrolyte may be mixed.
[0081] The cathode active material may be an oxide active material or a sulfide active material.
[0082] Examples of oxide active materials may include: 2 、LiMnO 2 、LiNiO 2 、LiVO 2 , Li 1+x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 Rock salt layer type active materials such as LiMn 2 O 4 、Li(Ni 0.5 Mn 1.5 ) 4Spinel active materials such as LiNiVO 4 、LiCoVO 4 Inverse spinel active materials such as LiFePO 4 、LiMnPO 4 、LiCoPO 4 、LiNiPO 4 Olivine-type active materials such as Li 2 FeSiO 4 , Li 2 MnSiO 4 Si-containing active materials such as LiNi 0.8 Co (0.2-x) Al x O 2 (0<x<0.2); spinel type active materials in which a portion of the transition metal is replaced by a different metal, such as Li 1+x Mn 2-x-y M y O 4 (wherein M is at least one selected from Al, Mg, Co, Fe, Ni, and Zn, 0<x+y<2); lithium titanate, such as Li 4 Ti 5 O 12 ,etc.
[0083] Examples of sulfide active materials may include copper Chevrel, iron sulfide, cobalt sulfide, nickel sulfide, and the like.
[0084] The solid electrolyte mixed in the cathode active material layer 40 may be substantially the same as the solid electrolyte included in the solid electrolyte layer 30 .
[0085] Examples of the conductive material may include carbon black, conductive graphite, vinyl black, carbon fiber, graphene, and the like.
[0086] Examples of the binder may include butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), and the like.
[0087] The cathode current collector 50 may include a plate-type substrate having electrical conductivity. Specifically, the cathode current collector 50 may be in the form of a sheet or a film. The cathode current collector 50 may include at least one selected from the group consisting of indium (In), copper (Cu), magnesium (Mg), aluminum (Al), stainless steel, iron, and combinations thereof. Specifically, the cathode current collector 50 may include aluminum foil.
[0088] The thickness of the cathode current collector 50 is not particularly limited, and may be, for example, 1 μm to 500 μm.
[0089] Method for manufacturing all-solid-state batteries
[0090] Another aspect of the present disclosure relates to a method for manufacturing an all-solid-state battery, comprising: preparing a porous network formed by intertwining fibrous carbon, obtaining an intermediate by immersing the network in a solution containing an inorganic electrolyte, obtaining a coating 20 by heat treating the intermediate, and obtaining an all-solid-state battery by stacking an anode current collector 10, a coating 20, a solid electrolyte layer 30, a cathode active material layer 40 and a cathode current collector 50, wherein the coating 20 may include the network and an inorganic electrolyte coating at least a portion of a surface of the network.
[0091] The porous network formed by entanglement of fibrous carbon can be prepared by a method generally used to synthesize sheet-type carbon materials. For example, chemical vapor deposition, especially direct spinning, can be used.
[0092] Direct spinning is a method of forming carbon nanotubes into fibers, which allows the synthesis of carbon nanotube fibers and is mainly used to synthesize fibrous carbon.
[0093] Direct spinning can be performed in such a way that a precursor solution including a material of fibrous carbon, a catalyst and a promoter, and a carrier gas are injected into an electric furnace of a vertical CVD (chemical vapor deposition) device at a predetermined rate to synthesize a carbon nanotube aerogel, and then the carbon nanotube aerogel is processed in a fiber form using a winding roller to obtain fibrous carbon. Here, the fibrous carbon can be obtained in a sheet form.
[0094] When the fibrous carbon is obtained by direct spinning, by controlling the material of the fibrous carbon, the temperature of the electric furnace, the winding speed of the winding roll, and the like, fibrous carbon having any shape, thickness, and porosity can be synthesized.
[0095] The material of the fibrous carbon may include a material selected from the group consisting of C 2 -C 10 At least one of the group consisting of saturated or unsaturated hydrocarbons, alcohols, and ketones. The catalyst may include at least one selected from the group consisting of ferrocene, copper (Cu), chromium (Cr), molybdenum (Mo), tungsten (W), iron (Fe), cobalt (Co), nickel (Ni), ruthenium (Ru), rhodium (Rh), palladium (Pd), osmium (Os), iridium (Ir) and platinum (Pt), and may particularly include ferrocene. The promoter may be thiophene or carbon disulfide. The carrier gas is not particularly limited as long as it is used to synthesize fibrous carbon using CVD or direct spinning, and for example, hydrogen (H 2 ).
[0096] In addition, when the fibrous carbon is obtained by direct spinning, the porosity of the fibrous carbon can be increased when the winding speed of the winding roll is increased. In addition, the porous network can be purchased on the market and used instead of being directly synthesized.
[0097] The porous network thus prepared can be immersed in a solution containing an inorganic electrolyte to obtain an intermediate.
[0098] Here, the solution is obtained by dissolving an inorganic electrolyte in a solvent, and the solvent may include at least one selected from the group consisting of an alcohol solvent, an organic solvent, a reaction solvent, and a combination thereof.
[0099] The type of alcohol solvent is not particularly limited, and for example, ethanol etc. can be used. The type of organic solvent is not particularly limited, and for example, acetonitrile, xylene etc. can be used. The type of reaction solvent is not particularly limited, and for example, tetrahydrofuran etc. can be used.
[0100] Meanwhile, when preparing the solution, the solution may not include a binder or a conductive material.
[0101] In an exemplary embodiment, the solution may contain 0.3wt% to 5wt% of an inorganic electrolyte. If the amount of the inorganic electrolyte is less than 0.3wt% based on the total weight of the solution, the ionic conductivity of the manufactured coating 20 may be low. On the other hand, if the amount of the inorganic electrolyte exceeds 5wt%, the surface of the network may be excessively coated with the inorganic electrolyte, resulting in a very low porosity of the coating 20 and reduced energy density and battery capacity. Preferably, the solution may contain 1.0wt% to 1.5wt% of an inorganic electrolyte. When the concentration of the inorganic electrolyte falls within the above range, further improved battery life characteristics can be obtained.
[0102] When the network is immersed in the solution, the inorganic electrolyte contained in the solution may be uniformly distributed within the pores of the network and on the surface of the fibrous carbon.
[0103] In an exemplary embodiment, the network can be immersed in the solution for 5 to 30 minutes. If the immersion time of the network is less than 5 minutes, the inorganic electrolyte in the solution cannot be fully introduced into the pores of the network and introduced onto the surface of the fibrous carbon. On the other hand, if the immersion time of the network exceeds 30 minutes, the inorganic electrolyte may be excessively distributed in the pores of the network and on the surface of the fibrous carbon, so that the porosity of the coating 20 may be excessively reduced and the energy density and battery capacity may be reduced.
[0104] Thereafter, by removing the solvent through heat treatment of the intermediate, a coating layer 20 including the network and an inorganic electrolyte coating at least a portion of the surface of the network can be obtained.
[0105] In an exemplary embodiment, the heat treatment may be performed at 50° C. to 450° C. If the heat treatment temperature is lower than 50° C., the crystallinity of the inorganic electrolyte may be reduced and the ionic conductivity may be reduced. On the other hand, if the heat treatment temperature exceeds 450° C., the inorganic electrolyte may be removed in addition to the solvent, thereby reducing the ionic conductivity of the battery.
[0106] In addition, the heat treatment may be performed for 6 to 24 hours. If the heat treatment time is less than 6 hours, the solvent distributed in the pores of the network and on the surface of the fibrous carbon cannot be completely removed. On the other hand, if the heat treatment time exceeds 24 hours, the inorganic electrolyte may be removed in addition to the solvent, thereby reducing the ionic conductivity of the battery.
[0107] Meanwhile, in an exemplary embodiment, after the intermediate is obtained, drying may be further performed at room temperature. When the intermediate is dried at room temperature, the highly volatile solvent may be mainly removed.
[0108] After obtaining the coating layer 20 by heat-treating the intermediate, an all-solid-state battery can be obtained by stacking the anode current collector 10, the coating layer 20, the solid electrolyte layer 30, the cathode active material layer 40, and the cathode current collector 50. The method of obtaining an all-solid-state battery by stacking the anode current collector 10, the coating layer 20, the solid electrolyte layer 30, the cathode active material layer 40, and the cathode current collector 50 can be performed by a typical method used in the art.
[0109] In addition, since the various components of the all-solid-state battery manufactured by the above-mentioned manufacturing method are basically the same as the components described above, their detailed description will be omitted.
[0110] A better understanding of the present disclosure can be obtained through the following examples. However, these examples are only set forth to illustrate the present disclosure and are not to be construed as limiting the scope of the present disclosure.
[0111] Preparation Example 1
[0112] (1) A precursor solution is prepared by mixing ethylene glycol with acetone as a material of fibrous carbon, ferrocene as a transition metal source of a catalyst, and thiophene as a promoter.
[0113] The precursor solution and carrier gas (H 2 , 2,200 sccm) was injected into the electric furnace of the vertical CVD device at a predetermined rate, and a carbon nanotube sheet as a porous network formed by entanglement of fibrous carbon was synthesized by direct spinning. Here, the winding speed of the roll was appropriately adjusted so that the thickness of the carbon nanotube sheet was 10 μm.
[0114] (2) A solution was prepared by dissolving LPSCl as a sulfide-based inorganic electrolyte in a mixed solvent of ethanol, acetonitrile, and tetrahydrofuran. Here, the concentration of the inorganic electrolyte was set to 1.25 wt % based on the total mass of the solution.
[0115] (3) The carbon nanotube sheet was immersed in the solution for 30 minutes to obtain an intermediate, which was then taken out and dried at room temperature for 2 hours.
[0116] (4) Thereafter, the intermediate is heat-treated in a vacuum atmosphere at 100° C. for 6 hours, thereby obtaining a coating layer including a carbon nanotube sheet and an inorganic electrolyte, wherein at least a portion of the surface of the carbon nanotube sheet is coated with the coating layer.
[0117] Preparation Example 2
[0118] A coating layer was prepared in the same manner as in Preparation Example 1, except that during the solution preparation, the concentration of the inorganic electrolyte was set to 0.63 wt % based on the total mass of the solution.
[0119] Preparation Example 3
[0120] A coating layer was prepared in the same manner as in Preparation Example 1, except that during the solution preparation, the concentration of the inorganic electrolyte was set to 0.32 wt % based on the total mass of the solution.
[0121] Comparative Preparation Example 1
[0122] A precursor solution was prepared by mixing ethylene glycol with acetone as a material of fibrous carbon, ferrocene as a transition metal source of a catalyst, and thiophene as a promoter.
[0123] The precursor solution and carrier gas (H 2 , 2,200 sccm) was injected into the electric furnace of the vertical CVD device at a predetermined rate, and a carbon nanotube sheet as a porous network formed by entanglement of fibrous carbon was synthesized by direct spinning. Here, the winding speed of the roll was appropriately adjusted so that the thickness of the carbon nanotube sheet was 10 μm.
[0124] Comparative Preparation Example 2
[0125] A carbon nanotube sheet was manufactured in the same manner as in Comparative Preparation Example 1, except that the winding speed of the roll was appropriately adjusted so that the thickness of the carbon nanotube sheet was 20 μm.
[0126] Comparative Preparation Example 3
[0127] A carbon nanotube sheet was manufactured in the same manner as in Comparative Preparation Example 1, except that the winding speed of the roll was appropriately adjusted so that the thickness of the carbon nanotube sheet was 30 μm.
[0128] Comparative Preparation Example 4
[0129] A carbon nanotube sheet was manufactured in the same manner as in Comparative Preparation Example 1, except that the winding speed of the roll was appropriately adjusted so that the thickness of the carbon nanotube sheet was 5 μm.
[0130] Test Example 1-SEM imaging results
[0131] In order to determine whether the coating synthesized according to the manufacturing method of the present disclosure is configured so that the surface of the carbon nanotube sheet is properly coated with the inorganic electrolyte, the SEM imaging results of Preparation Example 1 and Comparative Preparation Example 1 are shown in Figure 2 and Figure 3 middle.
[0132] Reference Figure 2 and Figure 3 , the size of the carbon nanotube bundles increased from about 21.46 nm to 59.16 nm, and the surface roughness of the carbon nanotube bundles also increased, confirming that the coating was configured so that the surface of the network was properly coated with the inorganic electrolyte.
[0133] Test Example 2 - Analysis of Specific Surface Area and Porosity Using the BET Method
[0134] Figure 4 and Figure 5 The results of microscale (carbon nanotube bundle) BET specific surface area analysis of the coating according to Preparation Example 1 are shown. Figure 6 and Figure 7 The results of the microscale (carbon nanotube bundle) BET specific surface area analysis of the porous network according to Comparative Preparation Example 1 are shown respectively. In addition, the specific numerical values of the analysis results are shown in Table 1 below.
[0135] For the BET specific surface area analysis of Preparation Example 1 and Comparative Preparation Example 1, a known specific surface area measuring instrument (TESKO) was used.
[0136] [Table 1]
[0137] Preparation Example 1 Comparative Preparation Example 1 <![CDATA[Specific surface area (m 2 / g)]]> 203.60 224.58 Porosity (%) 50.29 60
[0138] Reference Figures 4 to 7 and Table 1, wherein the specific surface area and porosity of Preparation Example 1 in which the surface of the carbon nanotube bundle is coated with an inorganic electrolyte are measured to be lower than those of Comparative Preparation Example 1 which is not coated.
[0139] This is believed to be because the space in the fibrous carbon is reduced due to coating with an inorganic electrolyte. When the porosity of the coating is reduced in this way, the amount of lithium precipitated inside the coating can be reduced during charging of an all-solid-state battery, and the amount of lithium precipitated at the interface between the coating and the solid electrolyte layer can be increased. In short, the coating can function as an anode current collector.
[0140] Test Example 3 - Total Pore Area and Porosity Using Mercury Porosimetry
[0141] Figure 8 and Fig. 9 The results of analyzing the total pore area and porosity of the coating according to Preparation Example 1 using mercury porosimetry are shown. Fig.10 and Fig.11 Results of analyzing the total pore area and the porosity of the porous network according to Comparative Preparation Example 1 using mercury porosimetry are shown respectively. In addition, specific numerical values of the analysis results are shown in Table 2 below.
[0142] Therefore, the analysis was carried out on a macroscopic scale (carbon nanotube sheets) and using a known mercury porosimeter (AutoPore V, Micromeritics).
[0143] [Table 2]
[0144] Preparation Example 1 Comparative Preparation Example 1 <![CDATA[Total pore area (m 2 / g)]]> 59.35 94.79 Porosity (%) 95.4 96.9
[0145] refer to Figures 8 to 11 and Table 2, wherein the total pore area and porosity of Preparation Example 1 in which the surface of the carbon nanotube bundle was coated with an inorganic electrolyte were measured to be lower than those of Comparative Preparation Example 1 which was not coated.
[0146] This is considered to be because the total pore area and porosity of the entire carbon nanotube sheet are reduced due to uniform coating of the surface of the carbon nanotube bundle with the inorganic electrolyte.
[0147] Example 1
[0148] The coating layer according to Preparation Example 1 and a solid electrolyte layer including a sulfide-based solid electrolyte were stacked on a nickel (Ni) thin film as an anode current collector. The sulfide-based solid electrolyte used was Li 6 PS 5 The half-cell is manufactured by attaching lithium metal to the upper side of the solid electrolyte layer, followed by pressing.
[0149] Example 2
[0150] A half-cell was manufactured in the same manner as in Example 1, except that the coating according to Preparation Example 2 was used.
[0151] Example 3
[0152] A half-cell was manufactured in the same manner as in Example 1, except that the coating according to Preparation Example 3 was used.
[0153] Comparative Example 1
[0154] A half cell was manufactured in the same manner as in Example 1, except that the carbon nanotube sheet according to Comparative Preparation Example 1 was used.
[0155] Comparative Example 2
[0156] A half cell was manufactured in the same manner as in Example 1, except that the carbon nanotube sheet according to Comparative Preparation Example 2 was used.
[0157] Comparative Example 3
[0158] A half cell was manufactured in the same manner as in Example 1, except that the carbon nanotube sheet according to Comparative Preparation Example 3 was used.
[0159] Comparative Example 4
[0160] A half cell was manufactured in the same manner as in Example 1, except that the carbon nanotube sheet according to Comparative Preparation Example 4 was used.
[0161] Test Example 4 - Analysis of Cycling Characteristics by the Thickness of the Carbon Nanotube Sheet
[0162] In order to evaluate the effect of the thickness of the carbon nanotube sheet used for coating on the life characteristics of the all-solid-state battery, the area capacity and coulombic efficiency of the half-cell were measured by repeating the charge and discharge cycles for Comparative Examples 1 to 3. The charge and discharge were performed under the following conditions: temperature: 50 °C, current density: 1 mA cm 2 , capacity condition: 3.5mAh·cm 2 .
[0163] The results are shown in Fig.12 , where the Coulomb efficiency is plotted in Fig.12 , while the area capacity is depicted at the bottom.
[0164] Reference Fig.12 , when the thickness of the carbon nanotube sheet is 10μm, the life characteristics are optimal, and the life characteristics deteriorate rapidly as the sheet thickness increases. This is believed to be because, due to the low lithium ion conductivity of the carbon nanotube sheet, the late-embedded lithium is first deintercalated during charging and discharging, resulting in irreversible entrapment of lithium inside the sheet.
[0165] In addition, the area capacity and coulombic efficiency of the half-cell were measured by repeating the charge and discharge cycles for Comparative Example 4 under the same conditions as above. The results are shown in Fig.13 where the Coulomb efficiency is plotted in Fig.13 The top of the graph is shown, and the charge and discharge capacities are depicted at the bottom.
[0166] Reference Fig.13 , showing stable charge / discharge behavior until the start of charge and discharge (7th cycle), but from the 8th cycle, internal short circuit occurred and testing could not be performed. This is believed to be caused by internal short circuit, which is caused by the use of a thin carbon nanotube sheet relative to the capacity, resulting in a lack of space for lithium insertion and extraction.
[0167] Summarizing Test Example 4, it was confirmed that the area capacity and coulombic efficiency of the battery were optimal when the carbon nanotube sheet not coated with an inorganic electrolyte had a thickness of about 10 μm. Since these results are determined by the thickness of the carbon nanotube sheet, the same trend is expected even when coated with an inorganic electrolyte.
[0168] Test Example 5 - Analysis of Cycling Characteristics by Concentration of Inorganic Electrolyte
[0169] In order to evaluate the influence of the concentration of the inorganic electrolyte included in the solution, the cycle characteristics of the all-solid-state batteries according to Examples 1 to 3 were analyzed. Fig.14 and as shown in Table 3 below, where the Coulombic efficiency is plotted at Fig.14 The top of the graph is plotted at Fig.14 The bottom of the graph.
[0170] The charging and discharging were carried out under the following conditions: temperature: 50 °C, current density: 1 mA cm 2 , capacity condition: 3.5mAh·cm 2 .
[0171] [Table 3]
[0172] Classification Example 1 Example 2 Example 3 Initial Coulombic efficiency 90.0 89.1 92.7 Cycle times 58 26 13
[0173] Reference Fig.14 3, when the amount (concentration) of the inorganic electrolyte included in the solution was 1.25 wt %, the best lifespan characteristics were exhibited.
[0174] and, Fig.15 A comparison of the cycle characteristics of the all-solid-state batteries according to Example 1 and Comparative Example 1 is shown, wherein the Coulombic efficiency is plotted in Fig.15 The top of the graph is plotted, while the area capacity is plotted at the bottom. Charging and discharging were performed under the following conditions: temperature: 50 °C, current density: 1 mA cm 2, capacity condition: 3.5mAh·cm 2 .
[0175] Reference Fig.15 , the initial capacity and coulombic efficiency values of Example 1 and Comparative Example 1 are similar to each other, but as the number of charge and discharge cycles increases, the capacity and coulombic efficiency of Comparative Example 1 decrease rapidly. In addition, it can be confirmed that the life characteristics of Example 1 are greatly increased compared with Comparative Example 1.
[0176] Test Example 6 - Analysis of Room Temperature Operating Characteristics
[0177] In order to predict the possibility of room temperature operation of an all-solid-state battery including a coating according to the present disclosure, the cycle characteristics of the all-solid-state battery according to Comparative Example 1 at room temperature were analyzed. The results are shown in Fig.16 The charging and discharging were carried out under the following conditions: temperature: 25 °C, current density: 1 mA cm 2 , capacity condition: 3.5mAh·cm 2 .
[0178] Reference Fig.16 , Comparative Example 1, which only includes a porous network not coated with an inorganic electrolyte, also shows good cycle characteristics when operating at room temperature. Therefore, it is expected that the all-solid-state battery according to the present disclosure, which includes a coating configured so that the surface of the porous network is coated with an inorganic electrolyte, has better room temperature operation characteristics.
[0179] Test Example 7-Possibility of replacing the anode current collector
[0180] In order to predict whether the coating according to the present disclosure can replace the anode current collector, a solid electrolyte layer including a sulfide-based solid electrolyte was directly stacked on the carbon nanotube sheet according to Comparative Preparation Example 1. The sulfide-based solid electrolyte used was Li 6 PS 5 The half-cell is manufactured by attaching lithium metal to the upper side of the solid electrolyte layer, followed by pressing.
[0181] For the half-cell without anode current collector, the cycling characteristics at room temperature were analyzed. Fig.17 The charging and discharging were carried out under the following conditions: temperature: 25°C, current density: 1 mA·cm 2 , capacity condition: 3.5mAh·cm 2 .
[0182] Reference Fig.17, good cycling characteristics were observed at room temperature despite the fact that no separate anode current collector was used. In this regard, a typical anode current collector is used to transfer electrons from the outside to the anode active material or to emit electrons from the anode active material so that an electrochemical reaction can occur during battery charging and discharging. Therefore, high electrical conductivity is required.
[0183] Since the carbon nanotube sheet is known to have high electrical conductivity, good cycle characteristics are expected to occur even when the carbon nanotube sheet is used instead of a typical anode current collector such as a Ni thin film.
[0184] Therefore, when such a coating is used as an anode current collector, the coating is configured so that the surface of the porous network having improved electrical conductivity and ionic conductivity in a balanced manner is coated with an inorganic electrolyte, even better cycling characteristics can be expected compared to when a carbon nanotube sheet is used as the anode current collector.
[0185] As is apparent from the above description, according to the present disclosure, lithium is stably precipitated on a coating layer having high electrical conductivity and ionic conductivity, thereby suppressing the formation of lithium dendrites and / or dead lithium, thereby increasing the lifespan of an all-solid-state battery.
[0186] According to the present disclosure, since an anode active material capable of alloying with lithium is not used, charging and discharging of an all-solid-state battery can occur through oxidation / reduction reactions of lithium ions rather than alloying reactions of lithium, so that charging and discharging operations can be performed at a relatively low temperature.
[0187] The effects of the present disclosure are not limited to the above-mentioned effects. It should be understood that the effects of the present disclosure include all effects that can be inferred from the description of the present disclosure.
Claims
1. An all-solid-state battery, comprising: Anode current collector; A coating layer is disposed on the anode current collector; a solid electrolyte layer disposed on the coating layer; a cathode active material layer disposed on the solid electrolyte layer; as well as a cathode current collector, disposed on the cathode active material layer, Wherein, the coating comprises a porous network, and the porous network comprises fibrous carbon and an inorganic electrolyte.
2. The all-solid-state battery according to claim 1, wherein: The coating has a thickness of 5 μm to 30 μm.
3. The all-solid-state battery according to claim 1, wherein: The fibrous carbon includes at least one selected from the group consisting of carbon nanofibers, carbon nanotubes, vapor-grown carbon fibers, and combinations thereof.
4. The all-solid-state battery according to claim 1, wherein: The coating does not contain conductive material or binder.
5. The all-solid-state battery according to claim 1, wherein: The inorganic electrolyte is sulfur-based.
6. The all-solid-state battery according to claim 5, wherein: The sulfur-based inorganic electrolyte is lithium phosphorus sulfur chloride (LPSCl).
7. A method for manufacturing an all-solid-state battery, the method comprising: preparing a porous network formed by entanglement of fibrous carbon; obtaining an intermediate by immersing the porous network in a solution comprising an inorganic electrolyte; obtaining a coating by heat treating the intermediate; An all-solid-state battery is obtained by stacking an anode current collector, the coating, a solid electrolyte layer, a cathode active material layer and a cathode current collector, Wherein, the coating layer includes the porous network and the inorganic electrolyte coating at least a portion of the surface of the porous network.
8. The method according to claim 7, wherein: The porous network is prepared by direct spinning.
9. The method according to claim 7, wherein: The fibrous carbon includes at least one selected from the group consisting of carbon nanofibers, carbon nanotubes, vapor-grown carbon fibers, and combinations thereof.
10. The method according to claim 7, wherein: The solution does not contain a binder or a conductive material.
11. The method according to claim 7, wherein: The solution includes 0.3 wt % to 5 wt % of the inorganic electrolyte.
12. The method according to claim 7, wherein: The solution is obtained by dissolving the inorganic electrolyte in a solvent, and the solvent includes at least one selected from the group consisting of an alcohol solvent, an organic solvent, a reaction solvent, and a combination thereof.
13. The method according to claim 7, wherein: The inorganic electrolyte includes a sulfur-based inorganic electrolyte.
14. The method according to claim 13, wherein: The sulfur-based inorganic electrolyte is lithium phosphorus sulfur chloride (LPSCl).
15. The method according to claim 12, wherein: The alcohol solvent includes ethanol, and the organic solvent includes one selected from the group consisting of acetonitrile, xylene, and a combination thereof.
16. The method according to claim 12, wherein: The reaction solvent comprises tetrahydrofuran.
17. The method according to claim 7, wherein: The porous network is immersed in the solution for 5 to 30 minutes.
18. The method according to claim 7, further comprising: After obtaining the intermediate, the intermediate is dried at room temperature.
19. The method according to claim 7, wherein: The heat treatment of the intermediate is performed at 50° C. to 450° C. for 6 to 24 hours.
20. A vehicle comprising the all-solid-state battery according to claim 1.